The process of Metalúrgica Delta Internationalization: Analysis Based on the Strategy Tripod - Medeiros, Ana Karine Lima de; Menezes, Jane Costa de; Sousa Filho, José Milton de; Ogasavara, Mario Henrique (Revista de Administração da UFSM, 2018)
This article, theoretical and empirical, aims to analyze the process adopted by a company in the metallurgical and graphic industry regarding its internationalization strategy. Thus, a case study was conducted by a qualitative approach, based on Peng’s strategic tripod (2009). The main objective of this study is to investigate how was the process of internationalization of the company object of this study, based on market vision vs. RBV vs. institution (Peng’s tripod) and identify the factors that impacted in the results obtained. The analysis shows that, a priori, the decisions taken by the company were not guided in all aspects necessary for the adoption of an internationalization process and that there were no operational, financial and economic gains in the adopted strategy.